D ETERMINANTS OF FINANCIAL PERFORMANCE: A N EMPIRICAL STUDY ON MALAYSIAN ISLAMIC BANKS - Muhammad Ahmar Ali; Alias Mat Nor; Mohd Sollehudin Shuib; Mohd Sofian Mohammad Rosbi (Journal of Islamic, Social, Economics and Development, 2023)
The positioning of Islamic banks as economic or social entities has been prominently debated on a global scale as Islamic bank social practices are still being neglected following their current emphasis on financial performance. Hence, this study examines the determinants of financial performance of Malaysian Islamic banks. The study uses panel data analysis, whereby the annual reports of 16 Islamic banks in Malaysia were analysed over a 10-year period from 2010 to 2019. The independent study variables were represented by the six determinants: Shariah-compliant financing, Zakat, advertising, household financing, non-performing financing and operational efficiency. Meanwhile, the dependent counterpart was financial performance proxied by return on asset (ROA) and return on equity (ROE). Multiple regression models consisting of the random-effect and fixed-effect models are incorporated for data evaluation. The findings of the study show a significant influence of Shariah-compliant financing, Zakat, advertising and operational efficiency on financial performance represented by ROA; while the ROE model reports a significant influence of Zakat, advertising, non-performing financing and operational efficiency on ROE of the banks. The study outcomes offer pivotal insights for Islamic banks to improve financial performance in line with its real objectives to support stakeholder interests and facilitate the sustainable economic growth of banks.